Development of Linktree-Based Interactive Learning Media to Improve History Learning Outcomes - Fadliati Harna; Abdul Muin Sibuea; Samsidar Tanjung (RIRAI Publisher, 2024)
The aim of this research is to produce Linktree learning media products aimed at testing aspects of the feasibility, practicality, and effectiveness of Linktree-based interactive learning media to improve history learning outcomes in class XI MAN 2 Medan Model. The research and development method used is the ADDIE model. The research results show: (1) The material expert validation test is very feasible with 93.75%. (2) The validation test for media experts is very feasible at 95%. (3) validation test of learning design experts in the very feasible category with 100%. (4) Individual trials in very feasible criteria with 83.92%. (5) The small group trial criteria were very feasible, with 89.83%. (6) Field trials met very feasible criteria with 94.06%, with an overall average result of 93.02%. Then the results of the experiment using Linktree-based interactive learning media using the problem-based learning model approach in the experimental class had an average learning outcome of 89.9, while using Linktree-based interactive learning media with the cooperative learning jigsaw model approach in the control class had an average value of 83.8. Based on the independent T-test, the effectiveness test showed a Sig value. (2-tailed) 0.000 is <0.05, which means it is significant. It was concluded that the Linktree-based interactive learning media with the problem-based learning model approach was effectively used to improve history learning outcomes. Based on the N-Gain calculation, a result of 60.96 was obtained in the quite effective category.